2018
DOI: 10.3390/geriatrics3040093
|View full text |Cite
|
Sign up to set email alerts
|

Postural Strategy in Elderly, Middle-Aged, and Young People during Local Vibratory Stimulation for Proprioceptive Inputs

Abstract: Proprioceptive input may greatly affect postural stability. However, the proprioceptive postural strategy in elderly, middle-aged, and young people has not been investigated sufficiently. Hence, in this study, we aimed to investigate differences in proprioceptive postural strategies of elderly, middle-aged, and young people. The center of pressure displacement was determined in 23 elderly, 23 middle-aged, and 23 young people during upright stance on a balance board with their eyes closed. Vibratory stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 21 publications
(36 reference statements)
1
14
0
Order By: Relevance
“…This result supports that the NSLBP group relied more on LM input in the Vater-Pacini corpuscles for postural control. These results agree well with those of previous studies where significant differences in postural sways were found between elderly individuals and healthy young adults during quiet standing conditions [25]. Moreover, a decreasing trend in the proprioceptive function in lower leg was observed in the NSLBP group.…”
Section: Discussionsupporting
confidence: 93%
“…This result supports that the NSLBP group relied more on LM input in the Vater-Pacini corpuscles for postural control. These results agree well with those of previous studies where significant differences in postural sways were found between elderly individuals and healthy young adults during quiet standing conditions [25]. Moreover, a decreasing trend in the proprioceptive function in lower leg was observed in the NSLBP group.…”
Section: Discussionsupporting
confidence: 93%
“…Among the risk factors for falls, the postural strategy with an RPW at 30 Hz is considered an important risk factor. Additionally, trunk proprioceptive deficits have been attributed to reduced lumbosacral proprioception, which might be a causative factor in elderly people's postural sway during instability [27,28,29]. Thus, these results showed that fallers used the ankle strategy more to maintain an upright position, whereas non-fallers predominantly used both the ankle and hip strategies during vibratory stimulation of muscle spindles.…”
Section: Discussionmentioning
confidence: 94%
“…COP excursion was recorded using a balance board (Wii; Nintendo Co., Ltd., Kyoto, Japan) [5,[16][17][18][23][24][25]. Balance board data were acquired using a sampling frequency of 100 Hz and calculated using MATLAB (MathWorks, Inc., Natick, MA, USA).…”
Section: Muscle Vibrationmentioning
confidence: 99%
“…Each subject's COP excursion was measured under six conditions, that is, two muscles × three frequencies of vibratory stimulation: 1 LM. The measurement time was 30 s, which was divided into two intervals of 15 s each [5,[16][17][18]. Vibratory stimulation was applied to the participants during the last 15 s. We labeled the first 15 s as "Pre" and the last 15 s as "During."…”
Section: Muscle Vibrationmentioning
confidence: 99%
See 1 more Smart Citation